Mão na massa em uma perspectiva inclusiva no ensino de ciências: estratégia e implementação de uma proposta metodológica - SOUSA, Rayane Sabrina dos Reis de (Universidade Federal do Pará, 2023)
This master's thesis constitutes a research in the area of Science Teaching with a focus on students with Intellectual Disability (ID) and aimed to build a pedagogical alternative, based on the methodological proposal Mão na Massa based on activities that favor access scientific knowledge to all students. The investigation took place in a municipal school, and involved both students with intellectual disabilities and effective science teachers from the teaching network. This research is qualitative in nature, applied and descriptive research. As for data collection and analysis procedures, document analysis and content analysis according to Bardin were adopted. In the development of the research, we present some theoretical notes on inclusive education, intellectual disability and the use of more active learning proposals in science teaching, in the sense of enabling students with disabilities to develop skills and abilities in the construction of scientific knowledge. The investigation stages took place in three distinct moments: the characterization of the evaluation and learning process of the researched students, the creation of a notebook in digital format (e-book) composed of five didactic sequences (educational product), as well as the evaluation and validation of this material by professors in the area. The results showed that the enrollment of students with disabilities is a reality in the educational scenario, which requires changes in the attitude of the school and in the pedagogical practice of its teachers, making it possible to highlight the weaknesses in the inclusion process. Regarding the didactic sequences, the proposal was well accepted by the teachers, as the data analyzed in the light of the theoretical framework, successfully met the proposed evaluation items. The didactic sequences were made available to teachers with a view to asserting their applicability, so it is expected that the results of this study open space for new research to be carried out and strengthen actions in favor of building schools that value differences.